One-arm safety intervention study on community case management of chest indrawing pneumonia in children in Nigeria – a study protocol. Issue 1 (31st December 2020) - Counihan, Helen; Baba, Ebenezer; Oresanya, Olusola; Adesoro, Olatunde; Hamzat, Yahya; Marks, Sarah; Ward, Charlotte; Gimba, Patrick; Qazi, Shamim Ahmad; Källander, Karin
ABSTRACT: Current recommendations within integrated community case management (iCCM) programmes advise community health workers (CHWs) to refer cases of chest indrawing pneumonia to health facilities for treatment, but many children die due to delays or non-compliance with referral advice. Recent revision of World Health Organization (WHO) pneumonia guidelines and integrated management of childhood illness chart booklet recommend oral amoxicillin for treatment of lower chest indrawing (LCI) pneumonia on an outpatient basis. However, these guidelines did not recommend its use by CHWs as part of iCCM, due to insufficient evidence regarding safety. We present a protocol for a one-arm safety intervention study aimed at increasing access to treatment of pneumonia by training CHWs, locally referred to as Community Oriented Resource Persons (CORPs) in Nigeria. The primary objective was to assess if CORPs could safely and appropriately manage LCI pneumonia in 2–59 month old children, and refer children with danger signs. The primary outcomes were the proportion of children 2–59 months with LCI pneumonia who were managed appropriately by CORPs and the clinical treatment failure within 6 days of LCI pneumonia. Secondary outcomes included proportion of children with LCI followed up by CORPs on day 3; caregiver adherence to treatment for chest indrawing, acceptability and satisfaction of both CORP and caregivers on the mode of treatment, including caregiver adherence to treatment; and clinical relapse of pneumonia between day 7 to 14 among children whose signs of pneumonia disappeared by day 6. Approximately 308 children 2–59 months of age with LCI pneumonia would be needed for this safety intervention study.